Relationship between Social Support and Life Satisfaction of College Students: Resilience As a Mediator and Moderator - Guo, Yuan (ETHICS IN PROGRESS, 2018)
A total of 843 college students in Guangdong University of Foreign Studies were investigated using a social support evaluation scale, a resilience scale, and a life satisfaction evaluation scale. Results were analyzed using IBM® SPSS 21.0® and Amos 17.0. It was shown that there existed a positive correlation respectively among resilience, social support and life satisfaction. Social support predicted resilience positively and resilience partially mediated the association between social support and life satisfaction. Finally, resilience moderated the association between social support and life satisfaction; the higher the resilience level, the more significant the positive predictive effect of social support on life satisfaction. College students' life satisfaction is closely related to social support and resilience; resilience partially plays a mediating and moderating role between social support and life satisfaction.